Bilateral inferior petrosal sinus sampling with desmopressin. (26th June 2012) - Deipolyi, Amy R; Hirsch, Joshua A; Oklu, Rahmi
Abstract : In this technical note, the use of desmopressin to stimulate pituitary adrenocorticotropic hormone secretion in place of the commercially available corticotropin releasing hormone (CRH) in bilateral inferior petrosal sinus sampling is described. Although the use of CRH is the standard of practice, it is currently unavailable in the USA and desmopressin provides reliable results with no additional observed side effects.